Breast cancer knowledge and screening practices among women in selected rural communities of Nigeria (2012)
Globally, the devastation that befalls women diagnosed of breast cancer remains inestimable. Early detection remains a major effective approach that should be employed to combat the disease. The issue of concern, however, is whether women in the rural underserved areas are aware of these early detection methods. This study was designed to assess rural women’s awareness and knowledge of breast cancer and their screening practices. The study was a descriptive cross-sectional study utilizing self developed structured questionnaire. Reliability of the instrument was determined and alpha correlation values range between 0.81 and 0.95 for the different components of the questionnaire. Data was processed using descriptive analysis and associations tested with Chi-square at 5% level of significance. The results of the findings showed that 52.7% of the women had adequate knowledge about breast cancer risk factors and symptoms. Regarding the women’s awareness about breast cancer screening methods, 52.8 and 51.7% of women have heard about Breast Self-Examination (BSE) and Clinical Breast Examination (CBE) respectively. However, few numbers of respondents (3.9%) were aware about mammography and these are people who did it for the purpose of diagnosing breast problem. Majority of the women (72.8%) did not practice BSE which is the most readily available screening method. Considering the lack of sophisticated diagnostic technology such as mammography for breast screening in the rural areas, BSE provided a unique opportunity for the women to be breast aware and to identify breast problems which may constitute danger to their health in the future. Health care professionals, most especially those at the primary health care level, should enhance the women’s skills to use this simple procedure effectively to promote their health